The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/jnci/djr244
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Use and Brain Tumors in Children and Adolescents: A Multicenter Case-Control Study

Abstract: The absence of an exposure-response relationship either in terms of the amount of mobile phone use or by localization of the brain tumor argues against a causal association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 33 publications
5
124
0
10
Order By: Relevance
“…Other health effects [13]: There are a lot of controversies regarding brain tumors associated with mobile phone users, for and against [14], [15], [16], [17]. Mobile phones generate electromagnetic radiation in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Other health effects [13]: There are a lot of controversies regarding brain tumors associated with mobile phone users, for and against [14], [15], [16], [17]. Mobile phones generate electromagnetic radiation in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, additional evidence has accrued of an increased risk to children. in the cefalo study, using operator reported data, an or of 2.15 (95% CI 1.06-4.29) was reported for children of median age 13 with >2.8 years since time from first subscription, combined with an increasing risk with increase in years since first use, P-trend=0.001 (24). In addition, the CEFALO authors reported an ipsilateral risk with >4 years of cumulative duration of subscriptions, OR 3.74 (95% CI 1.19-11.77) in combination of an increasing risk with increasing years of use, P-trend=0.02.…”
Section: Glioma Meningioma ------------------------------------------mentioning
confidence: 98%
“…They directly mixed AgNPs with liquefied brain tissue, which was obtained from three different locations of the sample: the tumor, peripheral of the tumor and the healthy site of tissue samples. The dominant differences were seen of the ratio peaks at around 723cm −1 and 655cm −1 (I 723 /I 655 ) [85, 86]. …”
Section: Brain Cancermentioning
confidence: 99%
“…The particles then were modified with 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid in complex with Gd 3+ ((DOTA)-Gd 3+ ) using a maleimide linkage (maleimide-DOTA-Gd). By using this method, the authors subsequently demonstrated not only its ability to yield high resolution brain tumor imaging and visualization of the margins of an invasive tumor, but also its use intraoperatively for brain tumor resection and to check unremoved malignant remainders as a probe [85,87]. Diaz and his coworker applied transcranial focused ultrasound to achieve maximal surgical resection and facilitate passing of a multifunctional designed gold nanoparticle (this was created by them to label and track glioblastoma cells through blood brain barrier (BBB) which serves as a barrier to nanoparticle transition from the vascular lumen to the brain parenchyma).…”
Section: Brain Cancermentioning
confidence: 99%